Identifying a Novel Defined Pyroptosis-Associated Long Noncoding RNA Signature Contributes to Predicting Prognosis and Tumor Microenvironment of Bladder Cancer - Lu, Hongcheng; Wu, Jiajin; Liang, Linghui; Wang, Xinwei; Cai, Hongzhou (Frontiers in Immunology, 2022)
Abstract: Background Bladder cancer (BLCA) is a common malignant tumor of the urinary tract, which is the 6th most common cancer among men. Numerous studies suggested that pyroptosis and lncRNAs played an essential role in the development of cancers. However, the expression of pyroptosis-related lncRNAs in BLCA and their correlations with prognosis remain unknown. Methods In this study, we constructed a signature model via Cox univariate analysis and LASSO Cox regression analysis based on the data from The Cancer Genome Atlas (TCGA) database. The expression of 12 pyroptosis-related lncRNAs was also confirmed by qRT-PCR in BLCA cell lines. TIMER, XCELL, QUANTISEQ, MCPCOUNTER, EPIC and CIBERSORT R script were applied to quantify the relative proportions of infiltrating immune cells. Correlation coefficients were computed by Spearman analyses. The Kaplan–Meier method, Cox regression model, and log-rank tests were used to evaluate the prognostic value. The R package of pRRophetic was used to predict IC50 of common chemotherapeutic agent. Results A total of 12 pyroptosis-related lncRNAs with great prognosis value were identified. The expression was validated by qRT-PCR using four cancer cell lines. Then, 126 cases were identified as high-risk group and 277 cases were identified as low-risk group based on the cut-off point. Patients in the low-risk group showed a significant survival advantage. Furthermore, we found that age, gender, tumor grade, clinical stage, T stage, N stage and M stage were significantly related to the risk score. As well, based on the C-index values, a nomogram was constructed. The GSEA results showed that MAPK signaling, TGF-β signaling and WNT signaling were with important significance in high-risk group. Moreover, immune infiltration analysis showed that riskscore was positively correlated with M0 macrophages and M2 macrophages, yet negatively correlated with CD8+ T cells. Conclusions In conclusion, our study indicated that pyroptosis is closely connected to BLCA. Moreover, the score generated from risk signature based on 12 pyroptosis-related lncRNAs was evaluated this novel model under various clinical settings including survival, clinical pathological characteristics, tumor microenvironment, immune therapy and chemotherapy. It may offer a significant basis for future studies.